Genetic and non-genetic risk factors for early-onset pancreatic cancer - Nodari, Ylenia; Gentiluomo, Manuel; Mohelnikova-Duchonova, Beatrice; Kreivenaite, Edita; Milanetto, Anna Caterina; Skieceviciene, Jurgita; Landi, Stefano; Lawlor, Rita T; Petrone, Maria Chiara; Arcidiacono, Paolo Giorgio; Lovecek, Martin; Gazouli, Maria; et al. (Digestive and liver disease, 2023)
Background - Early-onset pancreatic cancer (EOPC) represents 5-10% of all pancreatic ductal adenocarcinoma (PDAC) cases, and the etiology of this form is poorly understood. It is not clear if established PDAC risk factors have the same relevance for younger patients. This study aims to identify genetic and non-genetic risk factors specific to EOPC. - Methods - A genome-wide association study was performed, analysing 912 EOPC cases and 10 222 controls, divided into discovery and replication phases. Furthermore, the associations between a polygenic risk score (PRS), smoking, alcohol consumption, type 2 diabetes and PDAC risk were also assessed. - Results - Six novel SNPs were associated with EOPC risk in the discovery phase, but not in the replication phase. The PRS, smoking, and diabetes affected EOPC risk. The OR comparing current smokers to never-smokers was 2.92 (95% CI 1.69-5.04, P = 1.44 × 10−4). For diabetes, the corresponding OR was 14.95 (95% CI 3.41-65.50, P = 3.58 × 10−4). - Conclusion - In conclusion, we did not identify novel genetic variants associated specifically with EOPC, and we found that established PDAC risk variants do not have a strong age-dependent effect. Furthermore, we add to the evidence pointing to the role of smoking and diabetes in EOPC.
Online verfügbar: 25. März 2023, Artikelversion: 25. September 2023
Gesehen am 30.01.2024